OPTIMALISASI PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KELURAHAN WONOKUSUMO KECAMATAN SEMAMPIR PEMERINTAH KOTA SURABAYA - Muhammad Rendy Yoga Pradana; V. Rudy Handoko; Eddy Wahyudi (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Public service as a form of service, both in the form of public goods and services which in principle is the responsibility of and is carried out by central or regional government agencies in the context of efforts to meet community needs and in the framework of implementing statutory provisions. Public services, especially in population administration services, are still a problem that needs comprehensive attention and resolution. In this context, if it is related to public services, population administration services are the obligation of the state through the administration of the existing government to provide services for population administration rights that are owned by every citizen. On the basis of the considerations described above, this research was conducted to find out the implementation of optimizing administrative services and to find out the supporting and inhibiting factors in optimizing population administration services in Wonokusumo village, Semampir sub-district, Surabaya city government. This study used descriptive qualitative method. This research method focuses on the discussion by comprehensive the entire data obtained into a research result based on a qualitative descriptive theory. The results of this study indicate that the aim of optimizing population administration services in the Wonokusumo sub-district is to achieve excellent service for each population administration service. In service work tools, it is necessary to add work tools to maximize population administration services so that people feel comfortable when application services are in progress in the population administration field, as well as other supporting attributes such as cleanliness of waiting rooms, air conditioning and others that can support good service congestion. In handling service complaints, it is necessary to improve the performance of its employees. Because it is very unfortunate if the facilities in the complaint service are complete but the service officers are still lacking in skills